Prevalence of blood transfusion transmitted infections (HIV, HCV, HBV, Syphilis & Malaria) among the blood donors in a specialized hospital - Akter, Nasrin (Pulse, 2024)
Background: Blood transfusion is a life-saving intervention but may be a good source of transmission of various infectious and parasitic diseases. To ensure safe blood transfusion, all donors are systematically screened for transfusiontransmissible infections (TTI) including Hepatitis B and Hepatitis C, HIV, malaria, and syphilis. Transfusion transmitted infections are one of the major side effects of blood transfusion. We can prevent them by history taking and physical examination of blood donors and proper screening of blood products. The aim of the present study was to analyze the TTI prevalence rate among blood donors through screening test. Materials and methods: A retrospective observational study was conducted at Evercare Hospital Chattogram from April 2021 to February 2024. Blood screening was done by Immuno-chromatographic test (ICT) and RPR card test method. Results: Over a period of 35 months total blood donation was 4,226. The overall prevalence of HBsAg, HCV, HIV, syphilis, and malaria were 0.35%, 0.07%, 0.0%, 0.04 % and 0.02% respectively. Most of the donors were male (99.53%) and directed donors (98.10%). Conclusion: It should be ensured that all reactive donors notify the reactivity of screened disease. It is also necessary to develop nationally acceptable guidelines for notification and follow-up of responsive donors. This infected product could have become a source of infection for hundreds of people. Nucleic acid amplification testing (NAT) must be applied to identify positive blood donors during the window period before sero conversion. Information to TTIs reactive donor is the best method to prevent the chance of repeated reactive donation. Pulse Vol.16, 2024 P: 31-33